Common inpatient hypoglycemia phenotypes identified from an automated electronic health record–based prediction model. (25th January 2019) - Choi, Yoonyoung; Staley, Ben; Soria-Saucedo, Rene; Henriksen, Carl; Rosenberg, Amy; Winterstein, Almut G
Abstract: Purpose: Common inpatient hypoglycemia risk factor patterns (phenotypes) from an electronic health record (EHR)-based prediction model and preventive strategies were identified. Methods: Patients admitted to 2 large academic medical centers who were in the top fifth percentile of a previously developed hypoglycemia risk score and developed hypoglycemia (blood glucose [BG] of <50mg/dL) were included in the study. Frequencies of all combinations of ≥4 risk factors contributing to the risk score among these patients were determined to identify common risk patterns. Clinical pharmacists developed clinical vignettes for each common pattern and formulated medication therapy management recommendations for hypoglycemia prevention. Results: A total of 401 admissions with a hypoglycemic event were identified among 1, 875 admissions whose hypoglycemic risk was in the top fifth percentile among all admissions that received antihyperglycemic drugs and evaluated. Five distinct phenotypes emerged: (1) frail patients with history of hypoglycemia receiving insulin on hospital day 1, (2) a rapid downward trend in BG values in patients receiving an insulin infusion or with a history of hypoglycemia, (3) administration of insulin in the presence of an active nothing by mouth order in frail patients, (4) repeated low BG level in frail patients, and (5) inadequate night-time BG monitoring for patients on long-acting insulin. The 5 themes jointly described 53.0% of high-risk patients who experienced hypoglycemia. Conclusion: Five distinct phenotypes that are prevalent in patients at greatest risk for inpatient hypoglycemia were identified.